Two-visit CAD/CAM milled dentures in the rehabilitation of edentulous arches: A case series - Anish Varkey John; George Abraham; Anumol Alias (Wolters Kluwer Medknow Publications, 2019)
Computer-aided design-computer-aided manufacturing (CAD-CAM) has now found its place in the field of removable prosthodontics with the advent of its use in the fabrication of complete dentures. The conventional technique, by injection or compression molding using heat-polymerized resins, requires cumbersome laboratory procedures and up to five patient visits. For patients with time constraints and clinicians with a higher throughput rate, the CAD-CAM approach with a digital workflow can reduce the number of appointments and ensure speedy delivery of the prosthesis. This article describes the rehabilitation of completely edentulous arches using the Baltic Denture System (Merz Dental GmbH®) in just two patient visits.